Corporate social responsibility and job satisfaction: the mediating mechanism of supervisor fairness and moderating role of gratitude. (25th October 2022) - Akram, Rabia; Mahmood, Shahid; Khan, Kanwal Iqbal; Asghar, Farwa
Despite increasing interest in corporate social responsibility (CSR) and its impact on employees' attitudes and behaviour, only a handful of literature is available discussing the micro-level of CSR. There is a dearth of studies concerning the underlying process and contingencies affecting the CSR activities of employees. We posited that employees' perception of CSR triggers the authorities to be fair in all activities, which positively affects employees' level of satisfaction. Relying on social exchange and heuristic fairness theories, this study investigates the mediating role of supervisor fairness among CSR and job satisfaction and moderation of gratitude. We empirically examine the relationships by collecting data from the employees of the banking sector of Pakistan. The result reveals that the link between CSR and job satisfaction is mediated by supervisor fairness and moderated by gratitude. This study provides implications for both academicians and practitioners. Theoretically, it contributes to the literature of micro-CSR by providing a deep lens on how and in what ways CSR influences employees' behaviour at the workplace.